Determination of lethal concentration (LC50) values of Cinnamomum zeylanicum hydrosol on carp fish - Gulec, Kucukgul A.; Altinterim, B.; Aksu, O. (Iranian Fisheries Science Research Inst-Ifsri, 2013)
In this study, lethal concentration (LC50) values of cinnamon hydrosol (Cinnamomum zeylanicum) on carp (Cyprinus carpio) were investigated. In practice, experimental setup was constituted 30 fish (a total of 180 fish with 30 control fish) to be placed in three replicates. Hydrosol was added into aquariums at the doses of 0.5, 1, 2.5, 5 and 10% and determined mortality times of carp exposed to these concentrations. Percentage death of fish calculated in these concentrations. Mortality was observed at all treatments exception of dose of 0.5 %. The results indicate that the hydrosol had swimming changes, lethargy, lack of breath and leaning to the depth of the aquariums at all of the concentrations. The results of regression analysis indicated that the mortality rate (Y) is positively correlated the concentration (X) having a regression coefficient (R) close to one in each case. While the 1 h LC50 value (with 95% confidence limits) of the safe dose of C. zeylanicum hydrosol was estimated at LC50=4.39%, 2 h LC50 value=2.629%, and 12 h LC50 value= 1.027%.
Keywords: Hydrosol; Cinnamomum zeylanicum; Mortality; Cyprinus carp